Are lions democrats? The impact of democratization on economic growth in Africa, 1980–2010. Issue 1 (2nd January 2016) - Carbone, Giovanni Marco; Memoli, Vincenzo; Quartapelle, Lia
Abstract : If we look back at the past two decades, timing seems to point to a close connection between democratic reforms and economic growth in sub-Saharan states. Most countries in the area introduced multiparty politics and made dramatic – if incomplete – democratic progress between 1990 and 1994. Quite strikingly, it is exactly from 1994 to 1995 (and particularly from 2000) that the region began to undergo a period of significant economic progress. Because of the undeniable temporal sequence experienced in the region – that is, first political reforms, then economic growth – some observers pointed to a nexus between democratic progress and economic performance. But is there evidence in support of a causal relationship? As of today, no empirical research has been conducted on the democracy–growth nexus in the early twenty-first century's so-called "emerging Africa". To fill this gap, we discuss the different arguments claiming an economic advantage of democracies, we present our theoretical framework and carry out an empirical analysis of the growth impact of political regimes in 43 sub-Saharan states for the entire 1980–2010 period. Our findings confirm that African countries, many of which had long suffered the combination of authoritarian rule and predatory practices, derived some economic dividends from democratic progress.